Fabrication and evaluation of Rb2Co(H2P2O7)2·2H2O/waterborne polyurethane nanocomposite coating for corrosion protection aspects. Issue 87 (4th December 2017) - Deyab, M. A.; Essehli, R.; El Bali, B.; Lachkar, M.
Abstract : Here we investigate the influence of new acidic pyrophosphate (Rb2 Co(H2 P2 O7 )2 ·2H2 O) (DP) incorporation in waterborne polyurethane (WBPU) coatings on the corrosion protection efficiency of WBPU coatings for carbon steel in 3.5% NaCl solution. Abstract : Here we investigate the influence of new acidic pyrophosphate (Rb2 Co(H2 P2 O7 )2 ·2H2 O) (DP) incorporation in waterborne polyurethane (WBPU) coatings on the corrosion protection efficiency of WBPU coatings for carbon steel in 3.5% NaCl solution. We used potentiodynamic polarization, electrochemical frequency modulation (EFM) and pull-off adhesion and O2 gas permeability measurements to measure the corrosion protection efficiency of the WBPU coating. The dispersion of the DP nano-particles into the WBPU matrix was characterized via TEM observations. We find that the corrosion resistance and mechanical properties of the WBPU coating increase with incorporation of DP nano-particles into the WBPU coating.